Public Investment and Public-Private Partnerships Addressing Infrastructure Challenges and Managing Fiscal Risks - Schwartz, Gerd; Corbacho, Ana; Funke, Katja (Palgrave Macmillan UK, 2008)
There are now increasing concerns about the need to upgrade public infrastructure, improve the delivery of public services, and explore new options for partnering with the private sector. This book looks at ways of strengthening the efficiency of public investment and managing the fiscal risks of public-private partnerships
Keywords: Banks and banking; Welfare economics; Macroeconomics